Isolasi dan Purifikasi Inhibitor α-amilase dari Biji Kacang Phaseolus vulgaris - Husin, Bahagiawati A. (Jurnal AgroBiogen, 2005)
Plant genetic engineering technologies enable of introducing insect resistance genes into crop plants. The cry genes, genes encoding for inhibitor of digestive enzymes of a target insect that were isolated from Bacillus thuringiensis can be used for this purpose. Seeds of common bean (Phaseolus vulgaris) contain a glycoprotein that inhibits activity of α-amylase of insects. A α-amylase inhibitor was purified from the common bean seeds. The purified α-amylase inhibitor was then fed to cowpea storage weevil, Callosobruchus maculatus. The results showed a lengthened larval development time inside the seed and caused mortality to the insect larvae. This experiment suggests that the α-amylase inhibitor gene from the common bean seed could be used as a candidate gene for genetic engineering of plant resistance to bruchid insects.